Is MRI screening for bone marrow oedema useful in predicting lumbar bone stress injuries in adult male professional cricketers? A New Zealand pilot study - Bell, J. A.; Nunnerley, J. L.; Shackel, D. F.; Coates, M. H.; Campbell, R. G.; Frampton, C. M.; Schouten, R. (Journal of Science and Medicine in Sport, 2023)
Objectives The aims were to (1) prospectively observe the incidence of bone marrow oedema in asymptomatic adult male domestic professional cricketers during a season and evaluate its relationship to the development of lumbar bone stress injury and (2) further understand the practicalities of implementing a Magnetic Resonance Imaging-based screening program to prevent lumbar bone stress injury in New Zealand cricket.